The The Role of Digital Libraries in Preservation and Accessibility of Climate Change Research and Policy Documents for Adult Learners and Community Development: A Case Study of University Libraries in Osun State, Nigeria - Adewale Titus Elewode; Abimbola Roseline Olawale-Jimoh (Paidagogia: Jurnal Pengajaran dan Pendidikan, 2026)
This study examined the role of digital libraries in preserving and making climate change research and policy documents accessible to Adult Learners and Community Development in Osun State, Nigeria. A descriptive survey design was employed, and data were collected from 92 respondents. Comprising librarians, digital preservation officers, faculty members, and ICT staff, A total of 92 staff members, comprising librarians and digital preservation officers, Faculty members, and ICT staff across four university libraries: Obafemi Awolowo University, Ile-Ife; Osun State University, Osogbo; Bowen University, Iwo; and Redeemer’s University, Ede. Of the 92 questionnaires administered, 77 were returned and found usable, representing an 83.05% response rate. The results revealed that the availability of climate change-related materials in the libraries was excellent (mean = 2.92), whereas accessibility was moderate (mean = 2.85). Significant challenges identified include poor internet connectivity (76%), high cost of maintaining digital preservation infrastructure (68%), inadequate funding (64%), and limited collaboration with external organizations (59%). The study concluded that improving digital preservation infrastructure and sustainable funding mechanisms are critical for enhancing access to climate change information. It is therefore recommended that university libraries invest in advanced digital preservation technologies, foster partnerships, and promote inclusive services for adult learners and community development.